A comprehensive review of soil remolding toughness determination and its use in the classification of fine-grained soils - O'Kelly, Brendan (My University, 2023)
The remolding toughness property of fine-grained soil has not been investigated that much, mainly because it has not lent easily to direct measurement, with soil toughness usually qualitatively described. In practical terms, as the plastic limit wP is approached, tougher soils require greater rolling effort during the wP test, such that plasticity and toughness properties can be used to distinguish those plastic soils having greater deformation resistance for various field applications. This state-of-the-art review paper presents a critical appraisal of soil remolding toughness determination and its limited use, to date, in the classification of fine-grained soils. The recent developments reviewed and critically assessed include mechanical thread rolling for nominal toughness measurement during the wP rolling-out procedure, various extrusion approaches, and proposed correlations between toughness and the plasticity index to liquid limit ratio. From statistical analysis of previously reported toughness–consistency limits data, some new correlations are introduced in the present paper. Soil classification using the traditional Casagrande plasticity chart is not entirely accurate for certain soil types in that one can observe soils that present high toughness (something typical of clay) being incorrectly classified as silt soil. From this perspective, a new toughness chart is introduced to augment (or for use instead of) the Casagrande plasticity chart in obtaining more reliable soil classification. This paper concludes with recommendations on future research efforts for routinely obtaining soil toughness measurements.
PUBLISHED
Part of Special Issue ?Geomaterials: Latest Advances in Materials for Construction and Engineering Applications?
Keywords: Extrusion; Plastic limit; Soil classification; Soil plasticity; Toughness; Workability; Smart & Sustainable Planet; Constitutive modelling in geotechnical engineering; EXTRUSION; Geotechnical Engineering; Geotechnics; PLASTICITY; Plastic limit; SOIL PROPERTIES; SOIL TYPE; Soil Mechanics; Soil Mechanics & Foundations; TOUGHNESS; fine grained soil; geotechnical; soil classification; soil plasticity; workability